2021
DOI: 10.1177/03000605211010631
|View full text |Cite
|
Sign up to set email alerts
|

Chest computed tomography imaging features in patients with coronavirus disease 2019 (COVID-19)

Abstract: Objective To analyze computed tomography (CT) features of symptomatic patients with coronavirus disease 2019 (COVID-19). Methods Ninety-five symptomatic patients with COVID-19 confirmed by reverse-transcription polymerase chain reaction from 1 May to 14 July 2020 were retrospectively enrolled. Follow-up CT findings and their distributions were analyzed and compared from symptom onset to late-stage disease. Results Among all patients, 15.8% had unilateral lung disease and 84.2% had bilateral disease with slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Zhou [11] et al described pleural effusion in 3.2% of COVID-19 patients while Grassi et al [9] observed it in 14.3% of cases. Darwish et al [12] found that during the first week of infection pleural effusion occurs only in 13.6% of patients. Xiao li et al [10], in regard to pleural effusion, reported a frequency of 14.3% and concluded that it was not significantly associated with COVID-19 pneumonia.…”
Section: Pleural Effusionmentioning
confidence: 99%
“…Zhou [11] et al described pleural effusion in 3.2% of COVID-19 patients while Grassi et al [9] observed it in 14.3% of cases. Darwish et al [12] found that during the first week of infection pleural effusion occurs only in 13.6% of patients. Xiao li et al [10], in regard to pleural effusion, reported a frequency of 14.3% and concluded that it was not significantly associated with COVID-19 pneumonia.…”
Section: Pleural Effusionmentioning
confidence: 99%
“… 5 Darwish also found peripheral, and right lower lobe predominance of ground-glass opacity progressing to consolidation. 6 Al-Umairi included over 4000 patients in a meta-analysis with the most frequent finding of ground glass and consolidative pulmonary opacities in a lower lobe peripheral distribution. 7 Karimian described peripheral opacities in 70% and peripheral and central opacities in 30% of 4598 COVID-19 infected patients.…”
Section: Distribution Of Pulmonary Pathology In Covid-19 Diseasementioning
confidence: 99%